ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGGANTIAN KANTOR AKUNTAN PUBLIK SECARA VOLUNTARY (Studi Empiris pada Perusahaan Keuangan yang terdaftar di BEI) - Firyana, Rachma Aulia; Septiani, Aditya (Diponegoro Journal of Accounting, 2014)
Auditor independence issue often triggers debate regarding auditor rotation. ThisÂ  auditorÂ  rotationÂ  isÂ  relatedÂ  withÂ  companyÂ  actionÂ  toÂ  doÂ  auditor switching. ThisÂ  researchÂ  aimsÂ  toÂ  knowÂ  empiricalÂ  evidenceÂ  asÂ  forÂ  factorsÂ  influencing auditor Â switchingÂ  onÂ  the financial firmÂ  listedÂ  inÂ  IndonesiaÂ  StockÂ  Exchange. The factors to be analysed in this research are managementÂ  change,Â  financialÂ  distress, client size,Â  firm size, and percentage of ROA changes. The data beingÂ  usedÂ  isÂ  from financial companyÂ  whichÂ  isÂ  listedÂ  in â€œBursa Efek Indonesiaâ€ (BEI) in 2007-2012 period. Data collecting method which used in this research is method purposive sampling, that based on criteria which has been determined before. Based on the method purposive sampling, research sample total is 115 companies. By using logistic regression,Â  thisÂ  researchÂ  triedÂ  toÂ  testÂ  effectÂ  ofÂ  managementÂ  changes, financialÂ  distress, client size, firm size, and percentage of ROA changes towards Auditor Switching.Â  Result of this research indicates that variable having which significantly effect the voluntary auditor switching are managementÂ  change,Â  firm size, and percentage of ROA changes. On the other hand, other variables like financialÂ  distress andÂ  client size do not have significant effect on company decision to do voluntary auditor switching.Â